2017
DOI: 10.1002/ep.12656
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic combustion of toluene with Pd/La0.8Ce0.2MnO3 supported on different zeolites

Abstract: Pd/La 0.8 Ce 0.2 MnO 3 catalysts supported on various kinds of zeolites (ZSM-5, MOR, NaY, and b) were prepared by incipient wetness impregnation method, and these catalysts were investigated by Brunauer-Emmett-Teller, X-ray diffraction analysis (XRD), Fourier transform infrared spectroscopy, and H 2 -temperature programmed reduction. The catalytic activity of these catalysts was tested for toluene catalytic combustion, and the support effect was investigated. It was found that the ZSM-5 is the best support tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 27 publications
(43 reference statements)
0
12
0
Order By: Relevance
“…311 Ce-based oxides are also regularly used as supports for perovskite. A series of CeO 2 materials with different morphologies (rods, cubes and polyhedrons) were synthesized by Wang et al 481 and utilized as supports for La 0.8 Ce 0.2 MnO 3 . The morphology of the CeO 2 was determined to have a critical influence on the activity of La 0.8 Ce 0.2 MnO 3 phase.…”
Section: Chemical Reviewsmentioning
confidence: 99%
“…311 Ce-based oxides are also regularly used as supports for perovskite. A series of CeO 2 materials with different morphologies (rods, cubes and polyhedrons) were synthesized by Wang et al 481 and utilized as supports for La 0.8 Ce 0.2 MnO 3 . The morphology of the CeO 2 was determined to have a critical influence on the activity of La 0.8 Ce 0.2 MnO 3 phase.…”
Section: Chemical Reviewsmentioning
confidence: 99%
“…Numerous studies have demonstrated that the catalytic activity of Pd-supported catalysts is closely related to the oxidation state of Pd (Li et al, 2011;Gil et al, 2015;Zhao et al, 2016;Weng et al, 2019;Zhao X. et al, 2019). Some authors proposed that metallic Pd was more active in VOC oxidation than its oxidized state (Tidahy et al, 2008;Huang and Leung, 2011;Wang et al, 2018a;Zhao X. et al, 2019), as it can provide more active sites for the oxidation of hydrocarbons (Jinjun et al, 2005). The superior catalytic performance of Pd/ TiO 2 for HCHO oxidation relied on the metallic Pd NP with a strong capacity for oxygen activation (Huang and Leung, 2011).…”
Section: Influence Of the Pd Chemical Statementioning
confidence: 99%
“…The superior catalytic performance of Pd/ TiO 2 for HCHO oxidation relied on the metallic Pd NP with a strong capacity for oxygen activation (Huang and Leung, 2011). The Pd 0 species were also found to be more active than PdO for o-xylene oxidation reaction (Wang et al, 2018a). Jeong et al reported that hydrogen-treated catalysts showed higher oxidation activities than air-treated catalysts for possessing more metallic Pd (Ihm et al, 2004).…”
Section: Influence Of the Pd Chemical Statementioning
confidence: 99%
“…Due to the good thermal stability, eco-friendly nature, and large SSA, zeolite has been used widely as support for catalysts. 14 Wang et al 15 loaded Pd/La 0.8 Ce 0.2 MnO 3 on different zeolites by incipient wetness impregnation and found that Pd/La 0.8 Ce 0.2 MnO 3 /ZSM-5 showed the best activity. Hosseinpour et al 16 combined HY zeolite with LaBO 3 (B = Co, Mn, Fe) as catalysts for cumene cracking.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with other zeolites like NaY, MOR, and Beta, ZSM-5 has more acid sites and higher reducibility, which are beneficial for the supports of efficient catalysts. 15 Because HZSM-5 zeolite has a special pore structure and large SSA, the active species could be highly dispersed on its surface and the catalytic activity could be improved. 19 To the best of our knowledge, there is no study of catalytic oxidation of CO with LaMnO 3 loaded on HZSM-5 zeolite.…”
Section: Introductionmentioning
confidence: 99%